Step
*
1
of Lemma
axiom-choice-quot-alt-proof
1. T : Type
2. X : Type
3. P : T ⟶ X ⟶ ℙ
4. ∀f:T. ⇃(∃m:X. (P f m))
5. ChoicePrinciple(T)
⊢ ⇃(∃F:T ⟶ X. ∀f:T. (P f (F f)))
BY
{ (UnfoldTopAb (-1) THEN (FHyp (-1) [-2] THENA Auto)) }
1
1. T : Type
2. X : Type
3. P : T ⟶ X ⟶ ℙ
4. ∀f:T. ⇃(∃m:X. (P f m))
5. ∀P:T ⟶ ℙ. (∀t:T. ⇃(P[t]) 
⇐⇒ ⇃(∀t:T. P[t]))
6. ⇃(∀f:T. ∃m:X. (P f m))
⊢ ⇃(∃F:T ⟶ X. ∀f:T. (P f (F f)))
Latex:
Latex:
1.  T  :  Type
2.  X  :  Type
3.  P  :  T  {}\mrightarrow{}  X  {}\mrightarrow{}  \mBbbP{}
4.  \mforall{}f:T.  \00D9(\mexists{}m:X.  (P  f  m))
5.  ChoicePrinciple(T)
\mvdash{}  \00D9(\mexists{}F:T  {}\mrightarrow{}  X.  \mforall{}f:T.  (P  f  (F  f)))
By
Latex:
(UnfoldTopAb  (-1)  THEN  (FHyp  (-1)  [-2]  THENA  Auto))
Home
Index